Global Burden of Major Depressive Disorder: Prevalence, Diagnosis, and Impact: A Comprehensive review - Marefa Tuz Zohora Lima; Tanvir Ahmed Tamim; Israt Jahan; Esaba Sadia; Fatema Tuz Zohora Toma (Emerging Trends in Metabolites, 2024)
In this review, we will discuss about the major depressive disorders on the basis of neurobiological changes. MDD, a prevalent psychiatric condition, manifests as a complex interplay of genetic, environmental, and physiological factors with a substantial impact on individuals and societies globally. Here the clinical assessment is fully based on diagnosis and the statistical manual for mental disorder, 5th edition (DSM-5). The pathophysiology involves Diagnosis alterations in neurotransmitter systems, dysregulation of the hypothalamic-pituitary-adrenal (HPA) axis, and inflammatory responses. Serotonin, dopamine, and norepinephrine imbalances contribute to mood disturbances, with the monoamine hypothesis highlighting the role of neurotransmitter deficiencies. Abnormalities in the HPA axis leads to hypersecretion of corticotropin-releasing factor (CRF) and cortisol, influencing stress responses in MDD. Additionally, inflammatory cytokines play a role in neuroinflammation, affecting neurotransmitter function and contributing to depressive symptoms. Power spectral analysis of electroencephalogram (EEG) signals reveals distinctive patterns, including altered delta, theta, alpha, and beta waves, providing insights into neural activity changes in MDD. Spectral asymmetry, particularly in frontal regions, further indicates neurobiological correlates of depression. Conventional treatments primarily include antidepressant medications and psychotherapy, although challenges in efficacy and tolerability exist. Understanding the multifaceted aspects of MDD is crucial for improving diagnosis, treatment, and overall mental health outcomes. Potential biomarkers, emerging therapies are considered as treatment response. By critically examining existing challenges and embracing innovative approaches, this review aims to contribute to the ongoing efforts in improving the treatment landscape for individuals grappling with Major Depressive Disorder.
Keywords: BDI; DSM-V; MDD; diagnosis; pathophysiology